TOMOGRAPHIC IMAGE PREDICTION DEVICE AND TOMOGRAPHIC IMAGE PREDICTION METHOD - KOMORI, Seisaku; KIMURA, Yuichi (2022)
A tomographic image prediction apparatus 1 includes an input unit 11, a prediction unit 12, an output unit 13, and a learning unit 14. The tomographic image prediction apparatus 1 inputs a tomographic image of a brain of a subject as an input image I1, and predicts a tomographic image of the brain of the subject after the acquisition of the input tomographic image by a deep neural network in the prediction unit 12, and outputs the predicted tomographic image as an output image 12. The tomographic image prediction apparatus 1 is capable of training the deep neural network using a tomographic image database 15. Thus, a tomographic image prediction apparatus and a tomographic image prediction method which are useful for planning a future treatment policy and the like for a subject are realized.